Immersion Effect of Estradiol-17β on Cannibalism of Asian Redtail Catfish (Hemibagrus nemurus) Post Larvae - Benny Heltonika; Agus Oman Sudrajat; Muhammad Junior Zairin; Widanarni Widanarni; Muhammad Agus Suprayudi; Wasmen Manalu; Yani Hadiroseyani (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The dose, duration of immersion, and time interval of immersion of the estradiol-17β affect the rate of cannibalism and increase the seed survival of Asian redtail catfish in low treatment in this research. Over optimum treatment increased the incidence of cannibalism at Asian redtail catfish and decrease growth performance. Treatment of estradiol-17β, give the ability of Asian redtail catfish to live on high density The treatment of estradiol-17β, has an effect on concentration plasma of body testosterone and cortisol Abstract The cannibalistic behavior of Asian redtail catfish greatly hampers the supply of these fish seeds, invoking the need to be controlled. Estradiol is one of the hormones that has been known to reduce cannibalistic behavior on fish. This study aimed to evaluate the effect of estradiol-17β immersion on the incidence of cannibalism in the rearing of post larvae of Asian redtail catfish. Post larvae was treated with a combination of doses of estradiol hormone 0, 1, and 2 ppm and immersion time of two and four hours with immersion intervals of three and six days with a completely randomized design. Each treatment had a fish density of 10 fish L-1, with mean size individual length of 6.73 ± 0.73 mm (three days of age after hatched), with four replications. Fish were fed with tubifex up until satiation point and reared for 30 days. The results showed that the administration of the estradiol-17β through immersion with a dose of 1 ppm for two hours and interval of six days was able to reduce the level of cannibalism and increase the survivability. A further increase in dose, immersion time, and interval had the opposite effect. Estradiol-17β immersion with certain dose, duration, and interval affected the rate of cannibalism, growth rate, and survival. Estradiol-17β immersion at a dose of 1 ppm for two hours and six days interval was the best to reduce the level of cannibalism and normal mortality in post larvae of Asian redtail catfish.